Harmless barium slag compound as well as preparation method and application thereof

Through the coordinated precipitation of soluble sulfates and barium slag in desulfurization gypsum, a harmless barium slag composite is formed, which solves the problems of high cost of barium slag treatment and high energy consumption, and realizes the harmless treatment and resource utilization of barium slag Utilization reduces pollution and meets drinking water standards.

CN119140577APending Publication Date: 2024-12-17GUIZHOU REDSTAR DEVING +1

Patent Information

Application Number
CN202411282541.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing harmless treatment methods of barium slag are costly and consume a lot of energy, so they cannot be industrialized, and the pollution of barium slag causes serious harm to the environment.

Method used

The soluble sulfate in desulfurization gypsum is used to coordinate precipitate with the barium ions in the barium slag, and the harmless barium slag composite is formed by grinding and standing curing, which reduces the pollution of the barium slag and realizes resource utilization.

Benefits of technology

The harmless treatment of barium slag has been achieved, the treatment cost is reduced, the process flow is simplified, and the compressive strength and leaching safety of barium slag have been improved, and the drinking water standards are met, and the coordinated resource utilization of solid waste and hazardous waste has been promoted. use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140577A_ABST
    Figure CN119140577A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste treatment, in particular to a harmless barium slag compound and a preparation method and application thereof. The preparation method comprises the following steps: grinding barium slag and desulfurized gypsum, mixing with water, and standing and curing to obtain a harmless barium slag compound; the mass ratio of the barium slag to the desulfurized gypsum is limited to be (1-10.1): 1; the mass ratio of the water to the mixture of the barium slag and the desulfurized gypsum is (0.18-0.32): 1; soluble sulfate provided by the desulfurized gypsum is used, free barium ions in the barium slag are fixed through precipitation, barium sulfate is formed, and harmless fixation is achieved. The leaching concentration (horizontal oscillation method) of heavy metal ions in the barium slag is lower than the drinking water standard and the hazardous waste identification standard, and harmless treatment of the barium slag is achieved. The problems of reduction, harmlessness and recycling of industrial solid waste (desulfurized gypsum) and hazardous waste (barium slag) can be solved, and collaborative resource utilization and environmental protection of the solid waste and the hazardous waste are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste treatment, and in particular to a harmless barium slag composite and a preparation method and application thereof. Background Art

[0002] Barium carbonate is an important chemical substance obtained from barite. my country mainly uses the carbonization reduction method to produce barium carbonate, producing about 700,000 tons per year, accounting for about 75% of the global output. During the production process, a large amount of barium slag is produced, which is a solid waste containing soluble barium ions, which is toxic and corrosive. The pollution coefficient of barium slag in the carbonization reduction process is about 0.8, that is, 0.8 to 1 ton of barium slag is produced for every ton of barium salt produced. At present, the annual discharge of barium slag in my country exceeds 1 million tons, and the cumulative total stockpile has exceeded 10 million tons.

[0003] In addition, the leaching rate of barium slag is as high as 92.8%, and the barium ion concentration in its leachate is usually 2-10 times higher than the pollution control standard for hazardous waste landfill, causing serious pollution to the soil, groundwater and environment. Long-term stacking of barium slag will occupy a large amount of land, may spontaneously combust and release SO2 gas at high temperatures, and produce yellow leachate containing sulfide after rainwater infiltration, which is toxic to the soil and groundwater. At the same time, barium ions enter the human body through the food chain, causing irreversible damage to human health and the natural environment.

[0004] Harmless treatment, also known as safe treatment, is a process that uses advanced technology and processes to reduce the biological or chemical harmful substances in toxic and hazardous wastes to a minimum, so as to reduce their potential harm to the environment and reduce waste emissions. The ultimate goal of this treatment process is to achieve effective resource utilization of waste, especially for toxic and hazardous industrial wastes. For barium slag, the main purpose of harmless treatment is to deal with the large amount of barium carbonate contained in it. Since barium carbonate will react with carbon dioxide and water to produce water-soluble barium bicarbonate when stored in the air for a long time, this substance may cause serious pollution to environmental factors such as water resources. Therefore, it is very important to treat barium slag harmlessly to prevent water-soluble barium salts from damaging the environment.

[0005] At present, the main methods for harmless treatment of barium slag are: sulfate fixation method, that is, by introducing a barium ion fixer containing soluble sulfate to treat the barium ions in the barium slag. Yuan Zhiyu et al. studied the harmless treatment of barium slag landfill in a barium carbonate chemical industry in Hubei. The experiment adopted the sodium sulfate neutralization method, using the SO4 2- Ba in barium slag 2+The two react with each other to form harmless barium sulfate precipitates, thereby reducing the pollution of barium slag and not introducing new impurities. This method achieves effective solidification and reduction of barium ions in barium slag, but the amount of barium slag is large, which requires a large amount of chemical agents, resulting in high treatment costs and inability to achieve industrial harmless treatment of barium slag; phosphogypsum co-treatment method, which is to mix barium slag and phosphogypsum in a certain proportion, spray water to control the moisture content, and then stir and mix. This method can effectively fix barium ions and reduce the release of harmful pollutants in phosphogypsum. However, the treatment process is complicated and requires the coordinated operation of multiple specific equipment, resulting in high energy consumption in the harmless process and greatly limiting the consumption of barium slag and phosphogypsum. Summary of the invention

[0006] The purpose of the present invention is to provide a harmless barium slag composite and its preparation method and application, understand and analyze the characteristics of barium slag and desulfurized gypsum, start from the concept of "waste treatment" and "waste into treasure", coordinate precipitation mechanism, use the effective ingredients in desulfurized gypsum to fix the soluble barium ions in barium slag, provide new technology for harmless treatment of barium slag, and solve other corresponding industrial solid waste problems. While achieving harmless treatment of barium slag, reduce the cost of harmless treatment of barium slag, simplify the process of harmless treatment, and provide raw materials for later barium slag resource technology.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a harmless barium slag composite, comprising the following steps:

[0009] The barium slag and desulfurized gypsum are ground and mixed with water, and then allowed to stand and solidify to obtain a harmless barium slag composite;

[0010] The mass ratio of the barium slag to the desulfurized gypsum is 1-10.1:1; the mass ratio of the water to the mixture of the barium slag and the desulfurized gypsum is 0.18-0.32:1.

[0011] Optionally, the specific surface area of ​​the ground barium slag is greater than or equal to 400m 2 / kg, the specific surface area of ​​the desulfurized gypsum after grinding is greater than or equal to 450m 2 / kg.

[0012] Optionally, the curing temperature is 20 to 60° C. and the curing time is 6 to 24 hours.

[0013] Optionally, the desulfurization gypsum is solid waste produced from a desulfurization workshop; and the barium slag is solid waste directly discharged from a barium salt chemical process.

[0014] Optionally, the barium slag includes the following components in parts by weight: 32 to 50 parts of SiO2, 5 to 40 parts of BaO2, 18 to 30 parts of SO3, 7 to 15 parts of Fe2O3, 1 to 5 parts of Na2O, 1 to 5 parts of Al2O3, 1 to 4 parts of CaO, 0.8 to 3 parts of K2O, 0.5 to 3 parts of MgO, 0 to 2 parts of TiO2, and 0.1 to 1 parts of P2O5.

[0015] Optionally, the desulfurized gypsum includes the following components in parts by weight: 45-50 parts of CaO, 40-50 parts of SO3, 0.3-2 parts of MgO, 0-1 parts of SiO2, 0-1 parts of Al2O3, 0-1 parts of Fe2O3, 0-1 parts of Na2O, 0-1 parts of Cl, and 0-1 parts of K2O.

[0016] The present invention also provides the harmless barium slag composite prepared by the preparation method of the harmless barium slag composite.

[0017] Optionally, the pH of the harmless barium slag composite is 6-9, the toxic leaching concentration of barium ions is less than 10 mg / L, and the 7d compressive strength is greater than 0.5 MPa.

[0018] The present invention also provides application of the harmless barium slag composite as a raw material for recycling barium slag.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention provides a harmless barium slag composite, which uses soluble sulfate provided by desulfurized gypsum to precipitate and fix free barium ions in barium slag to form barium sulfate, thereby achieving harmless fixation. The leaching concentration of heavy metal ions in barium slag (horizontal oscillation method) is lower than the drinking water standard and the hazardous waste identification standard, thereby achieving harmless treatment of barium slag. It can solve the difficult problems of industrial solid waste (desulfurized gypsum) and hazardous waste (barium slag) reduction, harmlessness and resource utilization, and promote the coordinated resource utilization of solid waste and hazardous waste and environmental protection.

[0021] The invention provides a preparation method of a harmless barium slag composite. The preparation method is simple, and desulfurized gypsum is used to synergistically recycle the barium slag that is difficult to comprehensively utilize. Multiple solid wastes are synergistically utilized, and the recycling rate of the barium slag and the desulfurized gypsum is improved. The harmlessness cost is low, and the process flow of the harmless treatment of the barium slag is simplified. Desulfurized gypsum is used as a solidifying raw material to truly treat waste with waste.

[0022] The desulfurization by-product selected in the present invention can not only provide stable sulfate radicals to participate in the chemical reaction of free barium ion solidification to generate stable sulfate minerals, but also has the function of stabilizing the pH value; for the sulfite in the barium slag, the desulfurization by-product can also drive its conversion into sulfate.

[0023] The present invention improves the compressive strength and leaching safety of the harmless barium slag composite by optimizing the ratio between the barium slag and the desulfurized gypsum and the chemical composition of the raw materials. The barium slag has low corrosiveness, and the leaching toxicity of the barium ions is harmlessly treated. The toxic leaching concentration of the barium ions meets the provisions of the GB5085.3-2007 standard and the drinking water standard. In addition, since the strength of the harmless barium slag composite is improved, raw materials can be provided for the later barium slag resource technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The process flow chart of preparing harmless barium slag composite of the present invention;

[0025] Figure 2 This is the phase composition diagram of the raw material barium slag of the present invention;

[0026] Figure 3 This is a phase composition diagram of the harmless barium slag composite barium slag of Example 9 of the present invention;

[0027] Figure 4 This is a phase composition diagram of the harmless barium slag composite barium slag of Example 10 of the present invention. DETAILED DESCRIPTION

[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0033] The "room temperature" and "normal temperature" mentioned in the present invention are all calculated as 25±2°C unless otherwise specified.

[0034] The present invention provides a method for preparing a harmless barium slag composite, comprising the following steps:

[0035] The barium slag and desulfurized gypsum are ground and mixed with water, and then allowed to stand and solidify to obtain a harmless barium slag composite;

[0036] In the present invention, barium slag and desulfurized gypsum are ground, mixed, stirred and solidified at a specific mass ratio and water-binder ratio, and the grinding is grinding the barium slag or desulfurized gypsum in a test grinder; the mixing is mixing the barium slag with the desulfurized gypsum; the stirring is mixing the barium slag with the desulfurized gypsum and then stirring them evenly; the solidification is placing the mixture in a mold and letting it stand for solidification after stirring and mixing evenly.

[0037] The present invention adopts a synergistic precipitation mechanism. After the barium slag and desulfurized gypsum are ground for a certain period of time, they are mixed at a specific mass ratio and water-binder ratio. The desulfurization byproducts in the desulfurized gypsum are used to fix the soluble barium ions in the barium slag, and insoluble barium sulfate precipitation is generated through chemical reaction to obtain a harmless barium slag complex. The desulfurized gypsum used in this method is solid waste produced from the desulfurization workshop; and the barium slag used is solid waste directly discharged from the barium salt chemical process, which realizes the effective harmless treatment of the barium slag, reduces the cost of harmless treatment of the barium slag, and simplifies the harmless treatment process.

[0038] In the present invention, the mass ratio of the barium slag to the desulfurized gypsum is 1 to 10.1:1, for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.;

[0039] The mass ratio of the mixture of water, barium slag and desulfurized gypsum is 0.18-0.32:1, for example, it can be 0.18:1, 0.2:1, 0.22:1, 0.23:1, 0.25:1, 0.26:1, 0.28:1, 0.30:1, 0.32:1, etc. The desulfurized gypsum barium slag composite obtained within this water-binder ratio range can achieve a good curing effect.

[0040] In the present invention, the specific surface area of ​​the ground barium slag is greater than or equal to 400m 2 / kg, preferably 400-500m 2 / kg, more preferably 420 to 480m 2 / kg, more preferably 450-460m 2 / kg, the specific surface area of ​​the desulfurized gypsum after grinding is greater than or equal to 450m 2 / kg, preferably 450-550m 2 / kg, more preferably 460-520m 2 / kg, more preferably 480-500m 2 / kg.

[0041] In the present invention, the specific surface area of ​​the raw material is increased by grinding, which can stimulate the activity of the material, reduce the difficulty of hydration, and improve the curing ability; on the other hand, it can improve the uniformity of the material.

[0042] In the present invention, the curing temperature is 20-60°C, preferably 25-50°C, more preferably 30-45°C, and more preferably 35-40°C, and the curing time is 6-24h, preferably 8-20h, more preferably 10-18h, and more preferably 12-16h.

[0043] In the present invention, the desulfurized gypsum is solid waste produced from the desulfurization workshop, mainly composed of converter flue gas desulfurization slag, hot blast furnace flue gas desulfurization slag, coal-fired boiler flue gas desulfurization slag and sulfur production tail gas desulfurization slag; fly ash and slag mainly come from the finished product workshop and energy center, produced by hot blast furnace and coal-fired boiler, and the composition is similar to natural gypsum, which is calcium sulfate dihydrate CaSO4·2H2O;

[0044] The barium slag is solid waste directly discharged from the barium salt chemical process, for example, from a barium carbonate production line, that is, the residual solid left when leaching barium sulfide clinker generated by mixed roasting of barite and anthracite, and its main components include: BaSO3, BaS, CaSO4, SiO2 and incompletely reacted BaSO4 components.

[0045] In the present invention, the barium slag and desulfurized gypsum used can be purchased from the market, or can be homemade, or can be derived from solid waste generated in the process, as long as the chemical composition requirements are met.

[0046] In the present invention, the barium slag includes the following components in parts by weight: 32-50 parts of SiO2, 5-40 parts of BaO2, 18-30 parts of SO3, 7-15 parts of Fe2O3, 1-5 parts of Na2O, 1-5 parts of Al2O3, 1-4 parts of CaO, 0.8-3 parts of K2O, 0.5-3 parts of MgO, 0-2 parts of TiO2, and 0.1-1 parts of P2O5. For example, it can be 32.7 parts of SiO2, 27.98 parts of BaO, 19.2 parts of SO3, 7.83 parts of Fe2O3, 3.82 parts of Na2O, 3.45 parts of Al2O3, 2.35 parts of CaO, 0.82 parts of K2O, 0.63 parts of MgO, 0.4 parts of TiO2, and 0.19 parts of P2O5.

[0047] In the present invention, the desulfurized gypsum includes the following components in parts by weight: 45-50 parts of CaO, 40-50 parts of SO3, 0.3-2 parts of MgO, 0-1 parts of SiO2, 0-1 parts of Al2O3, 0-1 parts of Fe2O3, 0-1 parts of Na2O, 0-1 parts of Cl, and 0-1 parts of K2O. For example, it can be 45.54 parts of CaO, 45.5 parts of SO3, 0.37 parts of MgO, 0.29 parts of SiO2, 0.11 parts of Al2O3, 0.55 parts of Fe2O3, 0.01 parts of Na2O, 0.02 parts of Cl, and 0.02 parts of K2O.

[0048] In the present invention, the chemical composition of the above-mentioned barium slag and desulfurized gypsum refers to the content of various metals or mineral elements in the form of oxides, and does not refer to the content of compounds of the barium slag or desulfurized gypsum in the form of oxides. In addition, the above chemical composition results can be obtained by conventional detection methods available in the art, such as typical fluorescence detection methods after or before burnout.

[0049] The present invention also provides the harmless barium slag composite prepared by the preparation method of the harmless barium slag composite.

[0050] The sulfate fixation method solidifies barium ions through chemical reactions, effectively reducing environmental risks, but the high cost due to the large amount of chemical agents required limits its industrial application. The phosphogypsum synergistic treatment method reduces the release of harmful substances by recycling two industrial by-products through resource recycling, but the treatment process is complicated and energy-intensive, which also limits its large-scale application. However, the present invention utilizes the raw materials in the chemical plant throughout the entire process, using only desulfurized gypsum to achieve multi-solid waste synergy, realizes the effective harmless treatment of barium slag, reduces the cost of harmless treatment of barium slag, and simplifies the harmless treatment process. The resulting harmless barium slag composite has a certain strength. By optimizing the raw material ratio, it can prepare for the regulation of raw material composition for pretreatment of subsequent resource products.

[0051] In the present invention, the pH of the harmless barium slag composite is 6-9, for example, 6, 7, 8, 9, etc., the toxic leaching concentration of barium ions is less than 10 mg / L, and the 7d compressive strength is greater than 0.5 MPa.

[0052] The present invention also provides application of the harmless barium slag composite as a raw material for recycling barium slag.

[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0054] In the embodiments of the present invention, the crystal structure, material composition and microstructure of the barium slag were analyzed using a German Bruker D8 ADVANCE X-Ray Diffractometer. The phase composition of the raw barium slag used in Examples 1-10 is as follows: Figure 2 As shown; the secondary X-ray was measured by XRF-1800 X-ray fluorescence spectrometer to analyze the material composition. The chemical composition of the raw barium slag used in Examples 1-10 is shown in Table 1, and the composition of the raw desulfurized gypsum used in Examples 1-10 is shown in Table 2.

[0055] Table 1 Chemical composition analysis of raw barium slag

[0056]

[0057] Table 2 Chemical composition analysis of raw desulfurized gypsum

[0058]

[0059] Example 1

[0060] 406.51 g of barium slag and 406.51 g of desulfurized gypsum were ground and mixed with water, allowed to stand, and cured at 60° C. for 6 h to obtain a harmless barium slag composite;

[0061] The mass ratio of the mixture of water, barium slag and desulfurized gypsum is 0.23:1; the barium slag needs to be ground to a specific gravity of 400m 2 / kg, desulfurized gypsum needs to be ground to a specific gravity of 450m 2 / kg; the pH value of the harmless barium slag composite is 7.

[0062] Example 2

[0063] The only difference from Example 1 is that 482.81 g of barium slag and 325.2 g of desulfurized gypsum are ground and mixed with water; the pH of the harmless barium slag composite is 7.

[0064] Example 3

[0065] The only difference from Example 1 is that 569.11 g of barium slag and 243.9 g of desulfurized gypsum are ground and mixed with water; the pH of the harmless barium slag composite is 8.

[0066] Example 4

[0067] The only difference from Example 1 is that 650.41 g of barium slag and 162.6 g of desulfurized gypsum are ground and mixed with water; the pH of the harmless barium slag composite is 6.

[0068] The leaching toxicity of the untreated barium slag in Examples 1 to 4 was tested according to the national standard (HJ / T 557-2010) "Solid Waste Leaching Toxicity Method-Horizontal Vibration Method", and the Ba leaching concentration in the barium slag was 1870045 ug / L.

[0069] The harmless barium slag composites prepared in Examples 1 to 4 were cast and cured to different ages for compressive strength and leaching toxicity tests. The test method was as follows:

[0070] According to GB17671-1999 "Test Method for Cement Mortar Strength", the size of the desulfurized gypsum barium slag compound is made into 30mm×30mm×50mm, and the curing is carried out for 7d and 28d at a temperature of 35°C and a humidity of more than 99.5%.

[0071] The molded test blocks with different curing ages were tested for leaching toxicity and compressive strength according to the Chinese standard (HJ / T 557-2010) “Method for leaching toxicity of solid waste-Horizontal vibration method” and the Chinese standard GB / T17671-1999 “Test method for cement-Strength determination” (MTCDS). The test results are shown in Tables 3 and 4.

[0072] Table 3 Example 1 to 4 Desulfurization gypsum barium slag composite Ba leaching concentration

[0073]

[0074]

[0075] Table 4 Compressive strength of desulfurized gypsum barium slag composite test block of Examples 1 to 4

[0076]

[0077] It can be seen from Tables 3 and 4 that the harmless barium slag composite prepared by the present invention using barium slag and desulfurized gypsum has significantly reduced leaching toxicity after 7 days and 28 days, and has good compressive strength, which can prepare for the raw material composition regulation for pretreatment of subsequent resource products.

[0078] Example 5

[0079] 390.61 g of barium slag and 390.61 g of desulfurized gypsum were ground and mixed with water, and allowed to stand for 16 hours at 40° C. to obtain a harmless barium slag composite;

[0080] The mass ratio of the mixture of water, barium slag and desulfurized gypsum is 0.28:1; the barium slag needs to be ground to a specific gravity of 400m 2 / kg, desulfurized gypsum needs to be ground to a specific gravity of 450m 2 / kg; the pH value of the harmless barium slag composite is 9.

[0081] Example 6

[0082] The only difference from Example 5 is that 487.81 g of barium slag and 312.5 g of desulfurized gypsum are ground and mixed with water; the pH of the harmless barium slag composite is 7.

[0083] Example 7

[0084] The only difference from Example 5 is that 569.11 g of barium slag and 234.38 g of desulfurized gypsum are ground and mixed with water; the pH of the harmless barium slag composite is 8.

[0085] Example 8

[0086] The only difference from Example 5 is that 650.41 g of barium slag and 156.25 g of desulfurized gypsum are ground and mixed with water; the pH of the harmless barium slag composite is 6.

[0087] The leaching toxicity of the untreated barium slag in Examples 5 to 8 was tested according to the national standard (HJ / T 557-2010) "Solid Waste Leaching Toxicity Method-Horizontal Vibration Method", and the Ba leaching concentration in the barium slag was 1870045ug / L.

[0088] The harmless barium slag composites prepared in Examples 5 to 8 were cast and cured to different ages for compressive strength and leaching toxicity tests. The test method was as follows:

[0089] According to GB17671-1999 "Test Method for Cement Mortar Strength", the size of the desulfurized gypsum barium slag compound is made into 30mm×30mm×50mm, and the curing is carried out for 7d and 28d at a temperature of 35°C and a humidity of more than 99.5%.

[0090] The molded test blocks with different curing ages were tested for leaching toxicity and compressive strength according to the Chinese standard (HJ / T 557-2010) “Method for leaching toxicity of solid waste-Horizontal vibration method” and the Chinese standard GB / T17671-1999 “Test method for cement-Strength determination” (MTCDS). The test results are shown in Tables 5 and 6.

[0091] Table 5 Example 5-8 Desulfurization gypsum barium slag complex Ba leaching concentration

[0092]

[0093]

[0094] Table 6 Compressive strength of desulfurized gypsum barium slag composite test blocks of Examples 5 to 8

[0095]

[0096] It can be seen from Tables 5 and 6 that the harmless barium slag composite prepared by the present invention using barium slag and desulfurized gypsum has significantly reduced leaching toxicity after 7 days and 28 days, and has good compressive strength, which can prepare for the raw material composition regulation for pretreatment of subsequent resource products.

[0097] Example 9

[0098] 1491g of barium slag and 149g of desulfurized gypsum powder were ground and mixed with water, allowed to stand, and cured at 20°C for 24h to obtain a harmless barium slag composite;

[0099] The mass ratio of the mixture of water, barium slag and desulfurized gypsum is 0.18:1; the barium slag needs to be ground to a specific gravity of 400m 2 / kg, desulfurized gypsum needs to be ground to a specific gravity of 450m 2 / kg; the pH of the harmless barium slag composite is 6.

[0100] Example 10

[0101] The only difference from Example 9 is that 1230 g of barium slag and 410 g of desulfurized gypsum are ground and mixed with water; the pH of the harmless barium slag composite is 8.

[0102] The leaching toxicity of the untreated barium slag in Examples 9 to 10 was tested according to the national standard (HJ / T 557-2010) "Solid Waste Leaching Toxicity Method-Horizontal Vibration Method", and the Ba leaching concentration in the barium slag was 1870045 ug / L.

[0103] The harmless barium slag composites prepared in Examples 9 to 10 were cast and cured to different ages for compressive strength and leaching toxicity tests. The test method was as follows:

[0104] According to GB17671-1999 "Test Method for Cement Mortar Strength", the size of the desulfurized gypsum barium slag compound is made into 30mm×30mm×50mm, and the curing is carried out for 7d and 28d at a temperature of 35°C and a humidity of more than 99.5%.

[0105] The molded test blocks with different curing ages were tested for leaching toxicity and compressive strength according to the Chinese standard (HJ / T 557-2010) “Method for leaching toxicity of solid waste-Horizontal vibration method” and the Chinese standard GB / T17671-1999 “Test method for cement-Strength determination” (MTCDS). The test results are shown in Tables 7 and 8.

[0106] Table 7 Compressive strength of desulfurized gypsum barium slag composite test block of Example 9-10

[0107]

[0108] Table 8 Example 9-10 Desulfurization gypsum barium slag composite Ba leaching concentration

[0109]

[0110]

[0111] It can be seen from Tables 7 and 8 that the harmless barium slag composite prepared by the present invention using barium slag and desulfurized gypsum has significantly reduced leaching toxicity after 7 days and 28 days, and has good compressive strength, which can prepare for the raw material composition regulation for pretreatment of subsequent resource products.

[0112] Figure 3 In Example 9, the harmless barium slag composite barium slag phase composition after forming is as follows, Figure 4 In Example 10, the harmless barium slag composite barium slag phase composition after forming is Figure 3 and 4 It can be seen from the XRD data that the main product phases are barium sulfate and a small amount of quartz. The test shows that the harmless system has a certain strength, and the heavy metal solidification effect is good. The leaching meets the standard limit of barium ions in drinking water quality (750ug / L).

[0113] Application Example 1

[0114] The harmless barium slag composite prepared in Example 1 of the present invention is applied to road base materials.

[0115] A road base material comprises the following components by weight: 86 parts of harmless barium slag composite, 14 parts of solid waste-based cementitious materials, and 14 parts of tap water.

[0116] The composition of solid waste-based cementitious materials by weight is: 6 parts slag, 3 parts steel slag, 1 part desulfurized gypsum, with a specific surface area of ​​500m 2 / kg; the particle size of harmless barium slag is below 4.75mm.

[0117] The preparation method of the above-mentioned road base material is:

[0118] (1) Weigh the harmless barium slag composite and solid waste-based cementitious material according to the mass ratio, mix them evenly, and then conduct a compaction test to measure the maximum dry density ρ max 1.98g / cm 3 , the best moisture content MC is 14%;

[0119] (2) weighing the harmless barium slag composite and the solid waste-based cementitious material and mixing them uniformly to obtain a mixture, adding water to the uniformly stirred mixture, and mixing them uniformly to obtain a mixture;

[0120] (3) The mixture is stirred evenly and poured into a mold, and the pavement base material is obtained after demoulding.

[0121] The pavement base material prepared as above is used for molding, the molded product is demoulded, and then placed in a standard curing box with a temperature of 20±1°C and a relative humidity of 95% for curing for 7d and 28d, and water curing for 1d for subsequent test.

[0122] The pavement base material prepared in Application Example 1 was used to prepare Ф50mm×50mm cylindrical specimens using a universal press according to the unconfined compressive strength test requirements for inorganic binder stabilized materials in the "Test Code for Inorganic Binder Stabilized Materials for Highway Engineering" (JTGE51-2009), with at least 6 specimens in each group; after preparation, it was sealed and placed in a curing box for curing (curing temperature of 20±1℃, curing humidity of 95%), and cured for 7d and 28d (immersed in water one day in advance). After completion, the moisture on the surface of the specimens was wiped off, and the compressive strength of the specimens was tested using a pavement strength meter. The test results are shown in Table 9.

[0123] Table 9 Compressive strength test results of the pavement base material prepared in Application Example 1

[0124]

[0125] It can be seen from Table 9 that the harmless barium slag composite prepared by the present invention can be used as a raw material for pretreatment of subsequent resource products, and can be applied to the preparation of pavement base materials to prepare pavement base materials with excellent compressive strength.

[0126] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a harmless barium slag composite, It is characterized in that The following steps are involved: The barium slag and desulfurized gypsum are ground and mixed with water, and then allowed to stand and solidify to obtain a harmless barium slag composite; The mass ratio of the barium slag to the desulfurized gypsum is 1-10.1:1; the mass ratio of the water to the mixture of the barium slag and the desulfurized gypsum is 0.18-0.32:

1.

2. The method for preparing a harmless barium slag composite according to claim 1, It is characterized in that The specific surface area of ​​the ground barium slag is greater than or equal to 400m 2 / kg, the specific surface area of ​​the desulfurized gypsum after grinding is greater than or equal to 450m 2 / kg.

3. The method for preparing a harmless barium slag composite according to claim 1, It is characterized in that The curing temperature is 20-60° C. and the curing time is 6-24 hours.

4. A method for preparing a harmless barium slag composite according to claim 2 or 3, It is characterized in that The desulfurized gypsum is solid waste produced from a desulfurization workshop; the barium slag is solid waste directly discharged from a barium salt chemical process.

5. The method for preparing a harmless barium slag composite according to claim 4, It is characterized in that The barium slag comprises the following components by weight: SiO 2 32-50 parts, BaO 25-40 parts, SO 3 18-30 parts, Fe 2 O 3 7 to 15 servings, Na 2 O1~5 parts, Al 2 O 3 1~5 parts, CaO 1~4 parts, K 2 O 0.8~3 parts, MgO 0.5~3 parts, TiO 2 0~2 parts, P 2 O 5 0.1~1 portion.

6. The method for preparing a harmless barium slag composite according to claim 4, It is characterized in that The desulfurized gypsum comprises the following components by weight: 45-50 parts of CaO, SO 3 40-50 parts, MgO 0.3-2 parts, SiO 2 0~1 parts, Al 2 O 3 0~1 parts, Fe 2 O 3 0~1 part, Na 2 O 0~1 part, Cl 0~1 part, K 2 O 0~1 portion.

7. The harmless barium slag composite prepared by the method for preparing the harmless barium slag composite according to any one of claims 1 to 6.

8. The harmless barium slag composite according to claim 7, It is characterized in that The pH value of the harmless barium slag composite is 6-9, the toxic leaching concentration of barium ions is less than 10 mg / L, and the 7d compressive strength is greater than 0.5 MPa.

9. Use of the harmless barium slag composite prepared by the method according to any one of claims 1 to 6 or the harmless barium slag composite according to any one of claims 7 to 8 as a raw material for barium slag resource utilization.

Citation Information

Patent Citations

  • Barium residue coal ash building block and production method thereof

    CN102531500A

  • Barium slag innocent treatment method

    CN108176700A

  • Wet grinding barium residue admixture, preparation method and applications thereof

    CN110255943A

  • Phosphorus slag silicon-aluminum-based cementing material and preparation method thereof

    CN110713354A

  • Method for preparing solid waste-based cementing material through ultra-low-carbon ultra-low-emission gradient grinding

    CN114180862A

Cited By

  • Barium slag harmless treatment method and application

    CN119972759A

  • Durable building material for resource utilization of solid waste barium slag and preparation method of durable building material

    CN121717589A

  • Green optimization method based on barium slag harmless treatment process

    CN122400277A

  • A green optimization method based on barium slag harmless treatment process

    CN122400277B